Empowering Orphaned and Underprivileged Youth through Quilted Fabric Craft Based on Three-Dimensional Geometry and Realistic Mathematics Education - Afnaria, Afnaria; Isnaini Rambe; Br. Sembiring, Metrilitna; Arba; Arimbi, Yundari (Society : Jurnal Pengabdian Masyarakat, 2026)
This community service program aimed to empower orphaned and underprivileged youth at Rumah Yatim Medan through an integrated approach combining mathematics education, creative skill development, and digital literacy. A total of 18 children from elementary to high school levels participated in two sessions of quilted fabric product-making and one session of digital marketing training. Using the Realistic Mathematics Education (RME) approach, participants learned three-dimensional geometry concepts—such as area, perimeter, and volume—through hands-on activities involving fabric measurement, pattern design, and product construction. In addition, participants were introduced to basic entrepreneurship through practical exercises in social media-based promotion. Evaluation was conducted using pre- and post-tests, which showed substantial improvement across three learning domains. The average score for mathematical understanding increased from 55 to 80, product-making skills from 50 to 82, and digital marketing awareness from 40 to 78. The instruments used demonstrated high internal reliability with a Cronbach’s Alpha of 0.906. The program also enhanced participants’ confidence, collaboration, and initiative. A shared digital gallery was created via social media as a platform for showcasing their products and continuing promotional practice. Shelter staff expressed strong support and commitment to sustaining the activity. This program demonstrates the potential of contextual, interdisciplinary education to foster academic, vocational, and digital competencies in marginalized youth, while supporting the achievement of SDG 4, SDG 8, and SDG 12